Sistem Pendukung Keputusan Pemilihan Smartphone Kelas Midrange 2023 dengan Menggunakan Metode MAUT - Afri Nirmalasari Halawa; Helfrida Hotmaria Sihite; Muhammad Syahrizal (Journal of Computing and Informatics Research, 2024)
Smart phones (HP) have become a basic need for society in various aspects of life, from communication, entertainment, information, to work. There are various kinds of cellphones on the market, with various features and specifications offered. The price of cellphones is getting more and more expensive, so consumers' needs for using cellphones are also different. Midrange cellphones are suitable for users who want a cellphone with fairly good specifications, but at a relatively affordable price. Midrange is a category of cellphone that is between the entry-level and high-end categories. Midrange cellphones usually have better specifications than entry-level cellphones, but are not as expensive as high-end cellphones. Therefore, an appropriate midrange class cellphone selection process is needed for people to get a cellphone that suits their needs at an affordable price. In the selection process for midrange class cellphones, a decision-making technique known as SPK (Decision Support System) is required. In this research, the MAUT method is used for the midrange class HP selection process. The level of importance of each criterion is determined by the researcher himself. The final result obtained is that the A5 is the highest midrange class cellphone with a final value (Ui) of 0.865. The second ranked alternative is A13 with a final value (Ui) of 0.857 and the third ranked alternative is A17 with a final value (Ui) of 0.657.